Pengembangan Prototipe Media Pembelajaran Pada Alat Peraga “Mobil Bertenaga Angin” - Wicaksiwi, Anisa Kartika; Mayangsari, Feby Deatri; Mahdiannur, Muhammad Arif; Subekti, Hasan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Experiential learning media initiatives in junior high school because students will more easily understand concepts through experimental activities compared to just listening to information from the teacher. The method used is a survey of students' interests and motivations after trying the media props